2020
DOI: 10.1007/s13300-020-00858-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Novel Coronavirus Infection: Implications for Treatment

Abstract: The novel coronavirus (severe acute respiratory syndrome coronavirus 2 [SARS-CoV-2]) outbreak originating in December 2019 has resulted in a worldwide pandemic affecting millions across almost 200 countries. People with diabetes appear to develop more severe forms of the disease and to require intensive care unit support and/or mechanical ventilation more frequently than those with other underlying medical conditions. The mortality rate among people with diabetes is also significantly higher than that among pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Moreover, both are significant comorbidities for many other diseases including COVID-19. [23][24][25] In this study, we found that the number of diabetes mellitus visits had shown minimal decrease in the four week average, yet the prevalence ratio surged 1.54 times higher than the comparison period. This was desirable as it indicated that the patients were still willing to come for follow-ups.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, both are significant comorbidities for many other diseases including COVID-19. [23][24][25] In this study, we found that the number of diabetes mellitus visits had shown minimal decrease in the four week average, yet the prevalence ratio surged 1.54 times higher than the comparison period. This was desirable as it indicated that the patients were still willing to come for follow-ups.…”
Section: Discussionmentioning
confidence: 51%
“…To date, several clinical and epidemiological studies have indicated higher risk of SARS-COV-2 infection in DM patients [19,20]. However, it is not yet known whether patients with underlying DM are more susceptible to SARS-COV-2 infection [21][22][23]. Some studies postulated that the angiotensin converting enzyme 2 (ACE2) may be the plausible explanation of the association between risk of SARS-COV-2 infection in DM, CKD and CVDs patients and COVID-19 severity [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium-glucose transport inhibitors (SGLT-2i) precipitate towards a reverse insulin/glucagon ratio, and thus higher rates of ketosis, likely to complicate clinical manifestations of COVID-19 infection [10]; therefore their administration should be kept to a minimum. Treatment with glucagon like peptide 1 receptor agonists (GLP-1RA), a safe and effective anti-diabetic option in general, has been associated with an upregulation of ACE-2 inhibitors, which implies a possible adverse effect on the severity of immune reaction related with the disease [10]. Thiazolidinediones (TZDs) regulate not only glucose levels but also immune system response, through activation of the peroxisome proliferator activated J o u r n a l P r e -p r o o f receptor-γ (PPARγ) [11].…”
mentioning
confidence: 99%
“…Although metformin is the gold standard first choice of treatment in DM, it has to be withheld as soon as suspicious symptoms arise, aiming to minimize the risk of lactic acidosis. Sodium-glucose transport inhibitors (SGLT-2i) precipitate towards a reverse insulin/glucagon ratio, and thus higher rates of ketosis, likely to complicate clinical manifestations of COVID-19 infection [ 10 ]; therefore their administration should be kept to a minimum. Treatment with glucagon like peptide 1 receptor agonists (GLP-1RA), a safe and effective anti-diabetic option in general, has been associated with an upregulation of ACE-2 inhibitors, which implies a possible adverse effect on the severity of immune reaction related with the disease [ 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation